APLIKASI SYIRKAH BERBASIS BAGI HASIL TANGKAPAN IKAN NELAYAN: PERSPEKTIF SOSIAL EKONOMI - Malahayatie Malahayatie; Suryani Suryani (IAIN PONOROGO, 2020)
This study aims to find out about the tradition of fishing revenue mudharabah systems and see various phenomena of poverty in fishermen in Banda Sakti District, Lhokseumawe city, Aceh. The method in this study uses descriptive qualitative methods with the type of research using field research. The results of the study revealed that the existing fisheries revenue sharing practices among fishermen in Banda Sakti District were viewed from two different regions and were led by two regional commander namely Kuala Pusong and Kuala Mamplam. Each region has a different production sharing practice. The practice of mudharabah syirkah application has been applied unwritten among the fishermen.Keywords: Syirkah, Mudharabah, Fishermen